2021
DOI: 10.3390/biom11121825
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Role of Flavonoids as the Treatment of Depression

Abstract: Depression is one of the most frequently observed psychological disorders, affecting thoughts, feelings, behavior and a sense of well-being in person. As per the WHO, it is projected to be the primitive cause of various other diseases by 2030. Clinically, depression is treated by various types of synthetic medicines that have several limitations such as side-effects, slow-onset action, poor remission and response rates due to complicated pathophysiology involved with depression. Further, clinically, patients c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 201 publications
0
11
0
1
Order By: Relevance
“…Indeed, several studies have suggested the role of sulpiride in altering the antidepressant-like activity of various plant extracts in rodents 66 , 73 as well as the influence of some flavonoids on the dopaminergic system. 74 , 75 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, several studies have suggested the role of sulpiride in altering the antidepressant-like activity of various plant extracts in rodents 66 , 73 as well as the influence of some flavonoids on the dopaminergic system. 74 , 75 …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several studies have suggested the role of sulpiride in altering the antidepressant-like activity of various plant extracts in rodents 66,73 as well as the influence of some flavonoids on the dopaminergic system. 74,75 The cholinergic system plays an important role in the regulation of central functions such as arousal, attention, cognition, and memory. The cholinergic neurons are connected to the hippocampus and the VTA, and are involved in function of the reward system and mood regulation.…”
Section: Figurementioning
confidence: 99%
“…Myrecetin [438], kaempferol [439], naringin [440], quercetin [441,442] and luteolin [443] beneficially modulating the colon microbiome. Flavonoids thus have a number of beneficial health promoting properties exerted through the gut-lung, gut-liver and gut-brain axes [444][445][446][447][448][449][450]. Functional screening of metagenome and genome libraries has also been employed to detect flavonoid-modifying enzymes that generate bioactive components from dietary flavonoids [451] and bacterial species that convert dietary flavonoids have been identified [450].…”
Section: Flavonoids the Gut Microbiome And The Gut-brain And Gut-lung...mentioning
confidence: 99%
“…Dari tabel di atas, dapat diketahui aktivitas antidepresan dari tumbuh-tumbuhan suku Asteraceae mayoritas berasal dari senyawa-senyawa golongan flavonoid, seskuiterpen lakton, dan triterpen pentasiklik. Dalam memberikan aktivitas antidepresannya, selain melalui mekanisme antioksidan, flavonoid diketahui juga mempengaruhi reseptor neurotransmisi, kadar BDNF, meningkatkan pertumbuhan saraf, menghambat aktivitas enzim tertentu, memodulasi saluran ion kalsium dan kalium, serta menjaga plastisitas otak dan mencegas disipasi potensial membran mitokondria (17). Pada penelitian-penelitian terdahulu, seskuiterpen lakton terbukti bertindak sebagai penanda farmakologis yang ditujukan untuk penyakit neurodegeneratif, termasuk efek seperti antidepresan, dengan mekanisme yang mungkin melalui pemblokiran reseptor GABA-A atau efeknya pada sistem glutamatergik (11).…”
Section: Tabel 2 Kandungan Senyawa Tumbuhan Suku Asteraceae Yang Memi...unclassified